Factors associated with filariasis infection in Sorsogon Province, Philippines - Llanto, Ritchie E. (1997)
An ecologic study was undertaken to described the spatial and temporal distribution of lymphatic filariasis and determine possible factors associated with filariasis infection. The study area chosen was the province of Sorsogon, Philippines where one of the 3 Filariasis Control Service Unit (FCSU) were operating. Data involved were mainly records reviewed from the FCSU (from 1984 to 1995) and data from the 1990 Census of Population and Housing (CPH) and 1991 Census of Agriculture (CA). The study was generally composed of the descriptive part wherein geographical information systems (GIS) technology was used and a statistical part where multiple regression analyses were utilized in identifying possible factors associated with lymphatic filariasis. Within a period of 12 years, the FCSU was able to examine a total of 195,332 individuals with an overall positivity rate of 2.68. However, these results came from the efforts of the FCSU which varies in the 16 municipalities of the province. One municipality was not covered within the period. Furthermore, results showed that existing databases were generally lacking in information and were incompatible with other routinely collected data. Regression analysis showed the possible significant association of age and sex distribution, total land area, housing materials and agricultural factors such as the presence of farms, number of abaca and banana plantations and their corresponding number of trees with filariasis infection rates.